CONSTRUCTION OF ROAD SUB-BASE BY USING INDUSTRIAL WASTE (International Journal of Engineering Sciences & Management Research, 2026)
The objective of the study was to evaluate the effectiveness and the behavior of red mud to be used as sub base and also sub grade for road construction. This paper describes the characteristic properties of Red Mud and possible use as a geotechnical material. Basics properties like Specific gravity, Particle size distribution, liquid limit, OMC and MDD are determined. Engineering properties like shear strength and CBR values are also determined in conformity with the Indian Standard Code and test results are discussed in geotechnical point of view. Using the OMC and MDD results, direct shear box test was carried out to obtain shear strength parameter c and ф and unconfined compression shear test was carried out to obtain unconfined compressive strength and shear strength.